Factors associated with thromboembolic events following cytoreductive surgery and hyperthermic intraperitoneal chemotherapy. Issue 7 (26th June 2017) - Rottenstreich, Amihai; Kalish, Yosef; Kleinstern, Geffen; Yaacov, Almog Ben; Dux, Joseph; Nissan, Aviram
Abstract : Background and Objectives: We investigated the risk factors, incidence, and role of thromboprophylaxis in the development of thrombosis following cytoreductive surgery with hyperthermic intraperitoneal chemotherapy (CRS/HIPEC). Methods: We reviewed data of patients with CRS/HIPEC in three hospitals. Results: Overall, 192 patients underwent CRS/HIPEC during 2007‐2016. Mechanical (thigh‐length pneumatic compression stockings) and pharmacologic thromboprophylaxis (40 mg enoxaparin daily, starting 12 h before surgery until discharge) was provided for all patients; and 116 (60.4%) also received an extended course of enoxaparin for 2‐4 weeks after discharge. Twenty‐six patients experienced thrombotic complications (13.5%) including portal‐splenic‐mesenteric venous thrombosis ( n = 11, 5.7%), pulmonary embolism ( n = 10, 5.2%), and deep vein thrombosis ( n = 5, 2.6%); most ( n = 21, 80.8%) occurred after hospital discharge. Univariate analysis identified Peritoneal Cancer Index, intraoperative transfusion requirement, operative blood loss, operative time, lengths of hospital, and intensive care unit stay, and lack of administration of anticoagulation at discharge as significantly associated with thrombosis. With multivariate analysis, only the lack of anticoagulation therapy at discharge remained significantly associated with thrombosis ( P = 0.0001). Conclusions: Thromboembolic complications are common following CRS/HIPEC. As significantly lower rates of thrombosis were found in patients who received an extended course of anticoagulation, we support its use for at least 2 weeks after discharge.